Needs Analysis of Project-Based Learning Model in Writing Paragraphs from EFL Students’ Perspectives - Ilham, Ilham (Journal of Languages and Language Teaching, 2024)
Need analysis is required to take place before developing writing material so that results meet the needs of the students who will use the material. This research aims to analyze a model of English Paragraph Writing material based on project-based learning for EFL learners. A quantitative method was applied in this study employing a questionnaire and semi-structured interview to collect the data from 35 students and three instructors of writing in the English department, at Universitas Muhammadiyah Mataram. The data were analyzed quantitatively using frequency and percentage, while the data from the interview were transcribed and analyzed qualitatively. The result showed that students need teaching materials with clear objectives, exercises for individuals and groups, and project-based learning that can be employed in paragraph writing material. Therefore, designing a model of teaching material for paragraph writing based on project-based learning is much needed. The findings of this study are useful for lecturers and stakeholders who want to design English paragraph writing teaching material. This study has the potential to bridge the gap by providing knowledge of the needs of students and recommendations for designing English paragraph writing materials.